Cultural symbols in wall paintings between Iraq and Italy: comparative study - Rana Hazim Saeed (Basrah Arts Journal, 2024)
The research titled (Cultural Symbols in Graffiti art between Iraq and Italy - A Comparative Study) deals with the diversity of cultural symbols, their metaphors, and methods of expressing them for each people and is divided into four chapters. The first represents the methodological framework and includes the research problem, its importance, purpose, limits, and definition of terms. The second includes the theoretical framework and includes three topics: an intellectual introduction to culture and its relationships, the historical and conceptual root of Graffiti art, and the symbolic representations of culture in Graffiti art. The third chapter included research procedures and analysis of its sample, which included three drawings from each country. The researcher concluded a number of results such as. 1. Cultural symbols In Iraqi Graffiti art are characterized by specific metaphors and are limited to concrete isolation walls. While in Rome Cultural symbols are subject to a wide field of reference and are spread throughout most of the city’s spaces. 2. Most cultural symbols In Iraqi Graffiti art are characterized by iconic shapes and descriptive colors. While in Rome Most of the symbols are written and symbolic forms and conventional colors based on the concept of difference, breaking expectations, and achieving shock. 3. Cultural symbols In Iraqi Graffiti art establish decorative formations that perform a recreational function that do not reveal awareness of the cultural role of the system. While in Rome Cultural symbols establish aesthetic formations that perform a cultural expressive function and are aware of the cultural role of the system. Which were discussed and conclusions drawn.